FAKTOR KETERTARIKAN MINUMAN KOPI KEKINIAN TERHADAP MINAT BELI KONSUMEN KALANGAN MUDA - Pramelani Pramelani (Unib Press Universitas Bengkulu, 2020)
Today's coffee drinks are rife among young people. Competition between the beverage business shops is evident from the emergence of a variety of unique coffee shops. For this reason, the authors are interested in examining factors of current coffee beverage interest in young consumers' buying interest. This research uses descriptive qualitative method. With a purposive sampling technique, respondents are drawn from young people in Jakarta who like coffee drinks. Based on the results of interviews and observations obtained in the field found that there are several factors of interest so that there is an interest in buying among young people namely the factors of a comfortable place, friendly service, good taste factor where many variants, factors of restaurant names and unique menu names make there an interest to be interested in buying. In addition, the price factor is quite affordable, packaging with creative and attractive design. In addition, personal, social and psychological factors were found to be one of the factors of interest in buying contemporary coffee drinks among young people.Keyword: interest factors, buying interest, young consumer